'You feel that?' Examining gay porn discourse as hegemonic discursive soundtrack. Issue 1 (2nd January 2023) - Dashiell, Steven
ABSTRACT: This paper analyzes the discursive patterns of discourse in gay pornography and theorizes how masculinities theories are involved in the interactions. In pornography, discourse can frame the notion of the sexual situation, but can also demonstrate an interaction between the actors who participate. I analyze gay pornography scenes from the company Men.com which take place between January and November of 2019. Data are collected on conversations that occur during the act of anal penetration, and who participates. I theorize the conversation that occurs represents a sort of hegemonic soundtrack, between the insertive/top partner and the bottom/receiver. I argue that in both cases, the insertive partner is always the 'leader' and the focus of the interchange. The interaction reflects the notion of a patriarchal interchange that serves as a background music, acknowledged implicitly by the viewer.